Risk Factors Correlated with Incidence of Low Birth Weight Cases - Anjas Dwi Purwanto (Universitas Airlangga, 2017)
The infant with Low Birth Weight (LBW) was one of the risk factors that contributed to the high infant mortality, especially in the neonatal period. About 17% from 25 millions birth each year in the world are infant with LBW. LBW could be caused by multifactor that were maternal factors (maternal age, birth interval, parity, anemia), social-economic and behaviour, fetus factor, placental factor, and environmental factor. The research aims was to analyze the risk factors correlated with incidence of LBW. This research was an observational  research with case-control design. The number of samples in this research were 120 mothers who delivered in working area of RSIA Kendangsari in 2014. The subjects were selected used systematic random method. The independent variabels in this research were maternal age, education level, employment status, birth interval, parity, age pregnancy, multiple pregnancy, hypertension, and anemia, while the dependent variable in this research was LBW. Based on correlation analysis used Chi-square test showed there were not significant correlation (p>0,05) between birth interval and parity with LBW cases and there were significant correlations (p<0,05) between age pregnancy, hypertension during pregnancy and anemia with LBW cases. Odds Ratio (OR) were 13,571 on age pregnancy, 2,224 on multiple pregnancy,2,753 on hypertension and 4,030 on anemia. The conlusion showed that the risk factors of LBW cases were age pregnancy, multiple pregnancy, hypertension and anemia. While maternal age, education level, employment status, birth intervaland parity were not had any correlation with LBW cases. Keywords: LBW, risk factors, babies, maternal, pregnancy